Sialylated oligosaccharides in mare and ass milk: preliminary results - Orlandi, Mario; Curadi, Maria Claudia; Monti, Lucia; Cattaneo, Tiziana Maria Piera (Progress in Nutrition, 2016)
In this preliminary investigation milk samples from 4 multiparous amiata asses and 5 half-breed mares belonging to the same farm located near Grosseto (Tuscany), feeding the same pasture, were collected and analyzed. Milk samples collection was performed in the first three mounths of lactation. Capillary electrophoresis (CE) analysis were performed to quantify 3-sialyllactose (3-SL) and 6-sialyllactose (6-SL). 3-SL and 6-SL highest amounts were found in mares samples (197.3 mg/L e 82.2 mg/L), while highest asses amounts were 45.1 mg/L and 49.8 mg/L respectively. 3-SL amounts were higher in all mares samples than in donkey samples; in mares samples 3-SL amounts were always higher than 6-SL.